A Randomized, Controlled Study Evaluating Effects of Saccharomyces boulardii in Adult Patients with Asthma - Dezfouli, Kavosh Ansari; Darban, Mahboubeh; Hemmati, Maral; Zahir, Mazyar; Kermanshahi, Mojtaba Soltani; Abdolshahi, Anna; Sadr, Hani; Bagheri, Bahador (Drug Research, 2025)
To determine the potential benefit of adding Saccharomyces boulardii (S. boulardii) probiotic supplementation to conventional treatments in asthmatic patients.In this randomized, double-blinded, and placebo-controlled trial 50 asthmatic patients were enrolled. The eligible subjects received either S. boulardii (N=25) or placebo (N=25) added to conventional treatments for three months. Spirometry parameters (FEV1, FVC, FEV1/FVC, and FEF 25–75%) and blood test parameters (CBC, eosinophil percentage, IgE, IL-5, ESR and CRP) were measured and compared at baseline and after treatment completion.The mean age was 39.22±12.55 years. As compared to baseline values, a significant improvement was noted in FEV1 in patients who received S. boulardii (p=0.026). Although the changes in FEV1, FVC, FEV1/FVC, and FEF 25–75% were comparable between the study groups, the differences were not statistically significant (p ˃ 0.05). In addition, patients who received probiotic showed lower levels of IL-5 and IgE in comparison with patients who received placebo.Our findings showed that the addition of S. boulardii to conventional treatments partially improved the pulmonary function and was associated with reductions in IgE and IL-5 levels.
Keywords: asthma; probiotics; saccharomyces boulardii; spirometry